Pengembangan Keterampilan Proses Sains Dasar melalui Aktivitas Eksperimen pada Pembelajaran IPAS - Anastasia Putri Agung Febriana; Peduk Rintayati; Jenny Indrastoeti Siti Poerwanti (Didaktika Dwija Indria, 2026)
The implementation of Natural and Social Sciences (IPAS) learning in elementary schools plays a significant role in developing students' basic science process skills. However, classroom instruction is still predominantly characterized by lecture and demonstration methods, resulting in limited student engagement in scientific activities. This study aimed to examine the effect of the experimental method on the basic science process skills of fourth-grade students in learning the topic of changes in the states of matter. This research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The sample was selected through cluster sampling, with SDN Wirogunan 02 serving as the experimental group and SDN Kertonatan 01 as the control group. Data were collected through pretests, posttests, observations, and documentation. Data analysis included descriptive and inferential statistics, consisting of the Shapiro–Wilk normality test, Levene’s test for homogeneity of variance, and an independent samples t-test to test the research hypothesis. The findings revealed a significant difference between the two groups. The experimental group achieved a mean posttest score of 80.00, whereas the control group obtained a mean score of 46.94. The hypothesis testing showed a significance value of p < .001, indicating that the experimental method had a statistically significant effect on students’ basic science process skills. These findings suggest that the experimental method is an effective instructional alternative for enhancing students’ active participation, conceptual understanding, and basic science process skills in elementary school IPAS learning.